The impact of sucralose and neotame on the safety of metal precipitation in electronic cigarettes - Yan, Xinyang; Chen, Zheng; Rong, Xianfang; Chen, Zhichao; Wu, Guanlin; Dong, Zeyi; Fu, Yao; Hai, Tao (Frontiers in Physiology, 2024)
This study investigated the impact of sweeteners on the release of heavy metals during the heating and atomization processes in electronic cigarettes. Based on a PG/VG base e-liquid with the addition of 2% and 5% neotame or sucralose, we quantitatively analyzed the impact of sweetener content on the levels of heavy metals such as Ni, Cr, and Fe in the e-liquid and aerosol after heating and atomization. Additionally, the heated e-liquid samples were used to culture SH-SY-5Y and Beas-2B cells, and their cytotoxic effects were assessed using the CCK-8 assay. The results indicated that the e-liquid with 5% sucralose had the highest average levels of heavy metals after heating and atomization, particularly nickel (13.36±2.50 mg/kg in the e-liquid and 12109±3229 ng/200 puffs in the aerosol), whereas the e-liquid with neotame had significantly lower average heavy metal content in comparison.Additionally, it was measured that the chloride ion concentration in the e-liquid with 5% sucralose reached 191 mg/kg after heating at 200°C for 1 hour, indicating that heating sucralose generated chloride ions, which reacted with metal components leading to heavy metal release. Cytotoxicity tests revealed that the base e-liquid without sweeteners exhibited the highest average cell viability after heating, at 64.80±2.84% in SH-SY-5Y cells and 63.24±0.86% in Beas-2B cells. Conversely, the e-liquid variant with 5% sucralose showed a significant reduction in average cell viability, reducing it to 50.74±0.88% in SH-SY-5Y cells and 53.03±0.76% in Beas-2B cells, highlighting its more pronounced cytotoxic effects compared to other tested e-liquids. In conclusion, sucralose in e-liquids should be limited to 2% or less, or replaced with neotame, a safer alternative, to minimize health risks.